Cooperação no desenvolvimento de atividades de modelagem na educação matemática - MENEZES, Rhômulo Oliveira (Universidade Federal de Mato Grosso, 2022)
This article is a cut of a master's thesis that sought to identify and analyze implications arising from the use of Digital Technologies in the development of Mathematical Modeling activities. In this section, we aim to analyze the cooperation between subjects (students and teacher) and digital technologies in the development of Mathematical Modeling activities. The research is of the qualitative type, in which powerpoint reports and presentations produced by students of the math course and audio and video recordings recorded by the mediating teacher in the development of three activities of Mathematical Modeling were analyzed. In this way, it was possible to describe the cooperation established between the mediating teacher, the students and the digital technologies, allowing us to infer that this triad set up a semantic network (complex cognitive mixes and cooperatives) around the themes investigated.